The Multiple Role of Silicon Nutrition in Alleviating Environmental Stresses in Sustainable Crop Production - Szilvia Kovács (Plants, 2022)
In addition to the application of macronutrients (N, P, K), there has been an increasing interest in studying the effects of different micronutrients on growth and development in plant populations under abiotic and biotic stresses. Experimental results have demonstrated the role of silicon in mitigating environmental stresses on plants (especially in silicon accumulating plant species). Furthermore, as the silicon content of soils available to plants can vary greatly depending on soil type, the many positive results have led to increased interest in silicon as a nutrient in sustainable agriculture over the last decade. The grouping of plant species according to silicon accumulation is constantly changing as a result of new findings. There are also many new research results on the formation of phytoliths and their role in the plants. The use of silicon as a nutrient is becoming more widespread in crop production practices based on research results reporting beneficial effects. Controversial results have also been obtained on the use of different Si-containing materials as fertilizers. Many questions remain to be clarified about the uptake, transport, and role of silicon in plant life processes, such as stress management. Future research is needed to address these issues. This review discusses the role and beneficial effects of silicon in plants as a valuable tool for regulating biological and abiotic stresses. Our aim was to provide an overview of recent research on the role and importance of silicon in sustainable crop production and to highlight possible directions for further research.